Tujuan Manusia dan Jalan untuk Mencapainya Menurut Advaita Vedanta - Anak Agung Raka Asmariani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Humans are social creatures and in social life and have various complex problems. Various problems that exist are very difficult to be solved. Sometimes it is very difficult for humans to focus themselves to find what is really sought in this life so that a thought arises what is the purpose of humans living in this world? In this study Vedanta philosophy is able to answer this question. This study discusses